Single-shot T2(*) measurement to establish optimum echo time for fMRI: studies of the visual, motor, and auditory cortices at 3.0 T. - Clare, S; Francis, S; Morris, P; Bowtell, R (2001)
The signal change in fMRI is dependent on the echo time and the rate of decay of transverse magnetization. The latter factor may vary across regions of the brain as a result of variations in field homogeneity. Previous measurements of the signal change with echo time have generally employed relatively slow multi-echo techniques, which may be sensitive to movement and habituation effects. Here a fast T(2)(*) measurement technique, involving the generation of six low-resolution echo planar images from a single FID, is described, and its use in the evaluation of the optimum echo time for visual, motor, and auditory fMRI experiments at 3.0 T is outlined.